Random X inactivation in the mule and horse placenta - Wang, Xu; Miller, Donald C.; Clark, Andrew G.; Antczak, Douglas F.

(untitled) (Genome Research, 2012)
In eutherian mammals, dosage compensation of X-linked genes is achieved by X chromosome inactivation. X inactivation is random in embryonic and adult tissues, but imprinted X inactivation (paternal X silencing) has been identified in the extra-embryonic membranes of the mouse, rat, and cow. Few other species have been studied for this trait, and the data from studies of the human placenta have been discordant or inconclusive. Here, we quantify X inactivation using RNA sequencing of placental tissue from reciprocal hybrids of horse and donkey (mule and hinny). In placental tissue from the equid hybrids and the horse parent, the allelic expression pattern was consistent with random X inactivation, and imprinted X inactivation can clearly be excluded. We characterized horse and donkey XIST gene and demonstrated that XIST allelic expression in female hybrid placental and fetal tissues is negatively correlated with the other X-linked genes chromosome-wide, which is consistent with the XIST-mediated mechanism of X inactivation discovered previously in mice. As the most structurally and morphologically diverse organ in mammals, the placenta also appears to show diverse mechanisms for dosage compensation that may result in differences in conceptus development across species.